2013
DOI: 10.1021/ic301512c
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Chemical Topology Study of the Water-Platinum(II) Interaction

Abstract: The "inverse hydration" of neutral complexes of Pt(II) by an axial water molecule, whose one OH-bond is oriented toward Pt, has been the subject of recent works, theoretical as well as experimental. To study the influence of the ligands on this non-conventional H-bond, we extend here our previous energy calculations, using the second-order Moeller-Plesset perturbation theory (MP2) method together with the Dolg-Pélissier pseudopotential for platinum, to various neutral complexes including the well-known chemoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
35
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 55 publications
6
35
0
Order By: Relevance
“…For this purpose, the RESP charges obtained on the isolated molecules and isolated metal complexes were used supposing that the partial charges remain constant during the rPES scan 21 and reproduce the electrostatic interaction reasonably. This assumption is consistent with the performance of the common MM/MD simulation techniques.…”
Section: Methodsmentioning
confidence: 99%
“…For this purpose, the RESP charges obtained on the isolated molecules and isolated metal complexes were used supposing that the partial charges remain constant during the rPES scan 21 and reproduce the electrostatic interaction reasonably. This assumption is consistent with the performance of the common MM/MD simulation techniques.…”
Section: Methodsmentioning
confidence: 99%
“…33 Bergès et al 20 Table 4), thus indicating closed-shell, electrostatic interactions. This same result is also observed in conventional organic hydrogen bonds, 33 in the referred Pt(II)··H-OH interactions 20,21 or in other studies on M···H-X systems 11,34 Nevertheless, and as stated before, 11,33,34 considering the values and signs of  It has been observed that a more negative value of H(r) is related to the decrease in the distance between the interacting atoms, both in certain specific organic hydrogen bonding systems 33,37 and in other non-bonded interactions. 38 In these specific hydrogen bonding systems the donor or proton acceptors are ylides 37 or organic acids, 33 and when known, the X···H distances have been shown to be very short.…”
Section: Synthesis and Characterization Of The Complexes [Pt(c 6 F 5 mentioning
confidence: 98%
“…[2][3][4] Thef ormer type of association is now well understood at both theoretical and heuristic levels. [5] Although the Pt II ···H interaction in complexes has been confirmed by ac ombination of experimental and theoretical means, [5][6][7] Au···H interactions,p articularly in complexes, cannot be discussed with confidence as yet. Thep roblem is that whereas interactions between proton donors and Au À ions are accepted as genuine hydrogen bonds, [8] most of the Au···H contacts reported in gold(I) complexes are compromised by virtue of concomitantly occurring "classical" hydrogen bonds,c onjugation influences,p referred ligand arrangements or packing effects in crystals that impose positioning of particular H-atoms.…”
mentioning
confidence: 99%
“…Taking our cues from comments by Brammer [12] and Martin [13] that am ore negative charge on the metal center would favor stronger hydrogen bonds,w ei nitially embarked on af undamental theoretical investigation to establish the strength of Au···H interactions in known anionic gold(I) complexes with water molecules as compared to those in gaseous Au À adducts;c alculations were also carried out using neutral gold(I) complexes bearing electron-donating ligands as potential proton acceptors.T he results destined as directive for future experimental work, also provide new bonding information and indicate estimates of stabilization achievable by variation of the ligand environment of gold. Theelectronic properties of the auride anion, Au À ,known as astrong proton acceptor in hydrogen bond formation, [3,12] were mimicked by anionic dihydride (1) [14] and dialkyl (2,3,4)complexes [15][16][17] of gold(I) as well as in neutral complexes (5)(6)(7)(8) [18,19] having as trong s-donor N-heterocyclic carbene (NHC) ligand installed at gold.…”
mentioning
confidence: 99%